Internal Threshold of Toxicological Concern (iTTC): Where We Are Today and What Is Possible in the Near Future - Ellison, Corie A.; Api, Anne Marie; Becker, Richard A.; Efremenko, Alina Y.; Gadhia, Sanket; Hack, C. Eric; Hewitt, Nicola J.; Varcin, Mustafa; Schepky, Andreas (Frontiers in Toxicology, 2021)
The Threshold of Toxicological Concern (TTC) is an important risk assessment tool which establishes acceptable low-level exposure values to be applied to chemicals with limited toxicological data. One of the next steps in the continued evolution of the TTC is to develop this concept further so that it is representative of internal exposures. This refinement of TTC based on plasma concentrations, referred to as internal TTC (iTTC), attempts to convert the chemical-specific external NOAELs (in mg/kg/day) in the TTC database to an estimated internal exposure. A multi-stakeholder collaboration formed, with the aim of establishing an iTTC suitable for human safety risk assessment. Here, we discuss the advances and future directions for the iTTC project, including: (1) results from the systematic literature search for metabolism and pharmacokinetic data for the 1,251 chemicals in the iTTC database; (2) selection of ~350 chemicals that will be included in the final iTTC; (3) an overview of the in vitro caco-2 and in vitro hepatic metabolism studies currently being generated for the iTTC chemicals; (4) demonstrate how PBPK modeling is being utilized to convert a chemical-specific external NOAEL to an internal exposure; (5) perspective on the next steps in the iTTC project.